2019
DOI: 10.1016/j.ijfoodmicro.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

New insights on Listeria monocytogenes growth in pressurised cooked ham: A piezo-stimulation effect enhanced by organic acids during storage

Abstract: The aim of the present study was to understand growth and survival responses of Listeria monocytogenes during the storage of high pressure processed (HPP) cooked ham formulated with organic acids to inhibit growth of the pathogen. Cooked ham batches were manufactured without organic acids (control), with potassium lactate (2.8% or 4%) or with potassium lactate and sodium diacetate (2.0% + 0.11% or 2.0% + 0.45%). Products were aseptically sliced and inoculated with 10 7 cfu/g or 10 2 cfu/g of either L. monocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Similar results were observed in the study of Hayman et al [20] in a variety of RTE meats inoculated with 4 log CFU/g of L. monocytogenes , where after HPP treatment (600 MPa/180 s/20 °C) L. monocytogenes was found sporadically present after enrichment for a storage period of 91 days at 4 °C. Reduction of 7 log units of a 3-strain cocktail of L. monocytogenes (7 log CFU/g initial inoculum level) was observed at 600 MPa/3 min on cooked ham in the study of Bover-Cid et al [40]. Yet, the cells that survived were able to initiate growth just after HPP treatment [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were observed in the study of Hayman et al [20] in a variety of RTE meats inoculated with 4 log CFU/g of L. monocytogenes , where after HPP treatment (600 MPa/180 s/20 °C) L. monocytogenes was found sporadically present after enrichment for a storage period of 91 days at 4 °C. Reduction of 7 log units of a 3-strain cocktail of L. monocytogenes (7 log CFU/g initial inoculum level) was observed at 600 MPa/3 min on cooked ham in the study of Bover-Cid et al [40]. Yet, the cells that survived were able to initiate growth just after HPP treatment [40].…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of 7 log units of a 3-strain cocktail of L. monocytogenes (7 log CFU/g initial inoculum level) was observed at 600 MPa/3 min on cooked ham in the study of Bover-Cid et al [40]. Yet, the cells that survived were able to initiate growth just after HPP treatment [40]. Schneinberg et al [41] reported that inoculated beef jerky which was treated with two cycles of HPP (550 MPa/60 sec/22 °C) resulted in a reduction of approximately 1 log of L. monocytogenes (7 log CFU/g initial inoculum level) and subsequently it increased during storage under vacuum packaging, in contrast to the other examined inoculated pathogens that exhibited a significant reduction in the population levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, screening methods to study the effect of antimicrobials to control the growth of LM on RTE meat products are laborious and expensive, since they typically require the use of whole food products, such as slices of deli ham (6,11,17). Antimicrobials and pathogen cultures are applied to the surface of the slice of ham.…”
Section:  Response Surface Methodology Was Used To Analyze Antimicromentioning
confidence: 99%
“…The combination of enterocin and HHP (400 MPa/10 min/ 17 • C) was successful in preventing the growth of L. monocytogenes and widening the shelf life of treated samples at 90 days in comparison with control samples. More recently, Bover-Cid et al [151] evaluated the elimination of spiked L. monocytogenes (10 7 CFU/g) in HHP-treated (600 MPa/3 min) sliced standard cooked hams. Standard hams were produced with organic acids and control samples without organic acids, but including potassium lactate and sodium diacetate.…”
Section: Cooked Pork Hamsmentioning
confidence: 99%